Case Report: Forensic Examination of Alleged Case of Abuse by the Biological Father - Sity Rahmatia Alimun; Andi St Nabila Nahdah; Alivia Dian Fahira; Muzammilia Nadraini; Aulia Putri Apriliani; Noor Qadrianti Ramadhani; Denny Mathius; Zulfiyah Surdam; Andi Millaty Halifah Dirgahayu (Jurnal EduHealth, 2025)
This study aims to analyze the results of a forensic examination of a victim of alleged sexual abuse by her own father, reported by the South Sulawesi Regional Police. The forensic examination was conducted at the Forensic Medicine Unit of a hospital in Makassar on a 21-year-old woman. The comprehensive examination by the forensic team revealed no signs of acute physical violence. This means there was no evidence of fresh wounds caused by blunt or sharp objects, nor any signs of recent sexual penetration. This is a crucial finding, indicating that the alleged violence reported did not leave any traces of recent or active physical violence at the time of the examination. However, another crucial finding was the presence of an old tear in the hymen. The presence of this wound indicates that an injury had occurred in that area and that the wound had healed. This wound to the hymen can originate from various causes, including but not limited to old trauma, previous medical procedures, or even wounds related to past violent incidents that have undergone a healing process. The discovery of this old wound to the hymen requires further interpretation and needs to be linked to the victim's medical history and testimony in more depth to understand its context and cause. Even though there are no signs of new violence, the presence of old wounds that have healed remains important information in the investigation process and forensic assessment of cases of alleged sexual violence.